Питання реконструкції соціального ладу катакомбного суспільства - Пустовалов, С.Ж. (Археологія, 1999)
У світлі особливостей станово-кастових суспільств світу у статті розглядаються основні моменти реконструкції соціального ладу катакомбного населення Північного Причорномор'я. На основе новых материалов и теоретических разработок автор прослеживает степень разложения первобытности и конкретизирует форму социальной системы катакомбного общества Северного Причерноморья, которое, по его мнению, является сословно-кастовым. Based on the new materials and theoretical investigation, the author observes the extent, to which the prehistoric period decayed, and determines the form of a social system of Catacomb culture on the Northern Black Sea Coastland; the author believes that the structure of this system was of class and caste nature.